Erythropoietin administration exerted neuroprotective effects against cardiac ischemia/reperfusion injury - Titikorn Chunchai; Nattayaporn Apaijai; Juthipong Benjanuwattra; Hiranya Pintana; Kodchanan Singhanat; Busarin Arunsak; Nipon Chattipakorn; Siriporn C. Chattipakorn (Elsevier, 2022)
Acute myocardial infarction (AMI) leads to cardiac dysfunction and also causes brain dysfunction and pathology. The neuroprotective effects of erythropoietin (EPO), the hormone controlling the production of red blood cells, have been shown in case of cerebral ischemic/reperfusion (I/R) injury. However, the effects of EPO on the brain pathologies induced by cardiac I/R injury have not been investigated. We hypothesized that the administration of EPO attenuates brain damage caused by cardiac I/R injury through decreasing peripheral and brain oxidative stress, preserving microglial morphology, attenuating hippocampal necroptosis, and decreasing hippocampal apoptosis, and hippocampal dysplasticity. Male Wistar rats (n ​= ​38) were divided into two groups, sham (n ​= ​6) and cardiac I/R (n ​= ​32). All rats being subjected to the cardiac I/R operation were randomly divided into 4 subgroups (n ​= ​8/group): vehicle, EPO pretreatment, EPO given during ischemia, and EPO given at the onset of reperfusion. The EPO was given at a dosage of 5000 units/kg via intravenous injection. Left ventricle function, oxidative stress, brain mitochondrial function, microglial morphology, hippocampal necroptosis, hippocampal apoptosis, and hippocampal plasticity were measured. EPO administration exerted beneficial anti-oxidative, anti-inflammatory, and anti-apoptotic effects on the brain against cardiac I/R. Giving EPO before cardiac ischemia conferred the greatest neuroprotection against cardiac I/R injury through the attenuation of LV dysfunction, decrease in peripheral and brain oxidative stress, and the attenuation of microglial activation, brain mitochondrial dysfunction, apoptosis, and necroptosis, leading to the improvement of hippocampal dysplasticity under cardiac I/R conditions. EPO pretreatment provided the greatest benefits on brain pathology induced by cardiac I/R.